Upaya Meningkatkan Kemampuan Membaca pada Anak Sekolah Dasar Negeri 060900 - Yarli, Yosi; Ritonga, Fajar Utama (Medan Resource Center, 2023)
This article aims to discuss efforts to improve reading skills in SD N 060900 children. Reading ability is something that needs to be learned and mastered. The ability to read functions to make it easier for someone to understand the contents of the text being read in a relatively short time. In practice, the teacher will divide students into several groups. The group was divided into three groups, namely students who could not recognize letters yet, students who had started to be able to spell and students who could read word by word. Reading ability quickly became the yardstick for forming groups. Groups that cannot recognize letters at all will be formed into one group, they are taught starting from basic learning, while the next group is a group that can spell, they will prohibit and improve so that they can spell writing proficiently, the next group is students who can already read a few words, they will remind you to read more of a few words in a piece of writing. This study used observation and interview methods, as well as direct reading practice. The results showed that the students' abilities at SDN 060900 had increased after implementing a reading learning system by grouping students based on age level, reading ability and outdoor learning.